Synthesis and in vitro anticancer properties of a novel neodymium(III) complex containing tungstogermanate and 5-fluorouracil. Issue 14 (18th July 2018) - Liu, Haibin; Zhou, Baoyang; Zhao, Ce; Zhang, Danfeng; Wu, Qingyin; Li, Zengqiang
Abstract: A novel neodymium(III) complex containing tungstogermanate and 5-fluorouracil, K11 (C4 H4 FN2 O2 )2 Nd(GeW11 O39 )2 ·15H2 O (FNdGeW), was synthesized and its structure was characterized by 1 H NMR, IR, XRD, and TG-DSC. The results indicated that FNdGeW had Keggin structure of hetereopolyanion and structure of 5-fluorouracil. The thermal analysis showed that FNdGeW decomposed at 255.3 °C. MTT tests were performed to study the anticancer activities against SGC-7901 and HepG2 cells. The results showed that FNdGeW and FGeW possessed higher anticancer activities than 5-fluorouracil. FNdGeW exhibited the highest anticancer activities against SGC-7901 cells (IC50  = 0.79 μmolL -1 ) and HepG2 cells (IC50  = 0.37 μmolL -1 ). Abstract :